Álvares de Azevedo: do lirismo romântico ao prenúncio do modernismo, em “Um cadáver de poeta” - Oliveira, Taís Fernandes (2018)
The present work aims at analyzing the poem Um cadáver de poeta, by Álvares de Azevedo, published in his Lira dos vinte anos in 1853, in light of the latest edition organized by the critic Darcy Ribeiro and taking into account the assumptions about Brazilian Romanticism. It also aims at establishing the transition between Romantic lyricism and the first glimpses of Modernism, through the investigation of the hybrid genre and characteristics of Modernism as tools in the construction of the creative process, since existing studies have hitherto focused on the biographical, religious, sociological and linguistic aspects of the poems. Our hypothesis is that, although there is a romantic man in Um cadáver de poeta, Álvares de Azevedo’s lyric poetry would also contain an anticipation of Modernism, conveyed in his use of a hybrid genre, free verse and critical language, leading to an analysis of the place of the poet within Brazilian society in the 19th century. The works that supported our research were: Historiografia da literatura brasileira: textos inaugurais, by Joaquim Caetano Fernandes Pinheiro; O Romantismo no Brasil, by Antonio Candido; and A consciência criadora na poesia brasileira: do barroco ao simbolismo, by Sérgio Alves Peixoto, following a qualitative approach, of basic descriptive exploratory and bibliographic nature. We conclude that our hypothesis is confirmed after all and that, despite its Romantic lyricism, Um cadáver de poeta foreshadows Modernism in its mixture of literary genres, free verse and critical language